PENGARUH INTERAKSI SOSIAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN ROKAN HULU - Armiza Putri (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2023)
The purpose of this study was to determine the effect of social interaction on job satisfaction, the effect of the work environment on job satisfaction and the effect of social interaction and the work environment simultaneously on job satisfaction. This research method is quantitative with the population used are employees of the Rokan Hulu Regency Youth and Sports Education Office and the sampling technique is saturated sampling or census where the total sample is 87 people. Data collection was carried out by interviewing the pre-survey and followed by distributing questionnaires. The social interaction variable has a positive and significant influence (X1) 0.04 <0.05 and tcount is greater than ttable 2,085 > 1,988. Therefore H0 is rejected and H1 is accepted. The work environment variable has a positive and significant influence (X2) 0.001 <0.05 and tcount is greater than ttable 3,565 > 1,988. Therefore H0 is rejected and H2 is accepted. Simultaneously social interaction and work environment have a significant effect with the results of the f test obtaining Fcount of 10,614 and Ftable of 3.10 so that Fcount > Ftable or 10,614 > 3.10 whereas with a significant level of 0.000% <0.05% then H0 is rejected and Ha is accepted. For future researchers, it is hoped that this can be used as a reference so that social interaction and the work environment are not only examined in one object.